China's First Infrared Occultation Spectrometer (GaoFen-5/AIUS) Monitoring Atmosphere Above Antarctic: Evaluation of Methane Profiles - Liu, Shuanghui; Li, Xiaoying; Xu, Jian; Shi, Hailiang; Guo, Yuhang; Zhang, Xingying; Ge, Shule; Wang, Yapeng; Wang, Hongmei; Cao, Xifeng; Rao, Lanlan; Shi, Jiancheng (IEEE journal of selected topics in applied earth observations and remote sensing, 2024)
The atmospheric infrared ultraspectral sounder (AIUS) is China's first infrared occultation spectrometer onboard the GaoFen-5 satellite. This instrument provides measurements in the near-infrared and mid-infrared spectral regions with a spectral resolution of 0.02 cm ^{-1} , monitoring key greenhouse gases like methane (CH _{4} ). In this study, we have developed a physics-based retrieval algorithm for accurately deriving CH _{4} mole fraction profiles from infrared absorption spectra. The retrieval algorithm is applied to the AIUS and successfully obtains CH _{4} mole fraction profiles from January to December 2019 over Antarctic. The validation results show that the retrieval algorithm has a satisfactory performance using AIUS measurements, with average relative standard deviation of the differences less than 7.2% throughout the altitude range of 10-70 km.